A model for secure knowledge sharing - Ismail Ahmad; Ewe, Hong Tat (IEEE Xplore, 2005)
Improvements made in digital data processing resulted in the ability to store knowledge objects in sharing systems in the form of documents, images, audio and even video streams. However, with the increasing reliance on online knowledge sharing technologies, there is also an increasing danger that knowledge objects stored in digital forms are subjected to concerted malicious and possible criminal attacks. Digital knowledge objects can become easy prey to tampering and modifications which may defeat the original intent for knowledge sharing as well as causing loss of confidence among users. The preservation of the integrity of digital knowledge objects becomes increasingly important now than ever and the need has come for technologies to safeguard the authenticity and integrity of such objects. This paper proposes a model to incorporate automated detection and recovery mechanisms for tampered knowledge objects to make sure that knowledge-processing resources continue to perform correct processing operations at all times.